Physical activity amongst hemodialysed patients – why lack of motivation to exercise is present? - Turoń-Skrzypińska, Agnieszka; Tomska, Natalia; Uzdzicki, Artur; Przybylski, Tomasz; Dutkiewicz, Grażyna; Rotter, Iwona (Pedagogy and Psychology of Sport, 2020)
In recent years a great interest in rehabilitation and physical activity amongst hemodialysed patients have developed. Despite having numerous exercise options, adverse effects of a lack of movement still are seen in this group of patients. The reasons of insufficient physical activity amongst hemodialysed patients are complications related to chronic diseases and renal replacement therapy. For patients suffering from kidney failure it is crucial to adhere to recommendations relating to regular physical activity in order to maintain health and good quality of life.